2023
DOI: 10.1002/ccr3.6901
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in activating calcium‐sensing receptor antibodies positive autoimmune hypoparathyroidism and preponderance of steroids therapy: A case report

Abstract: A 55‐year‐old female patient presented with generalized tonic–clonic seizures. Laboratory evaluation revealed low calcium (4.9 mg/dl), low PTH (0.9 pg/ml), and positive activating CaSR antibodies. The condition was diagnosed as autoimmune hypoparathyroidism. Calcium and vitamin D supplements did not correct the patient's hypocalcemia. The addition of prednisone to vitamin supplements showed a better response and corrected the hypocalcemia. The patient remained in seizure‐free for one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The desired therapeutic result is to maintain the serum calcium close to the lower limit of the normal range. 16 Evidence from prior case reports has suggested that correcting underlying abnormalities may improve the presenting symptoms in cases where metabolic disturbances are found. Since hypoparathyroidism is a common cause, we can set dietary regimens for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The desired therapeutic result is to maintain the serum calcium close to the lower limit of the normal range. 16 Evidence from prior case reports has suggested that correcting underlying abnormalities may improve the presenting symptoms in cases where metabolic disturbances are found. Since hypoparathyroidism is a common cause, we can set dietary regimens for the patient.…”
Section: Discussionmentioning
confidence: 99%